Aberrant Interhemispheric Connectivity in Obstructive Sleep Apnea–Hypopnea Syndrome - Liu, Yu-Ting; Zhang, Hui-Xin; Li, Hui-Jun; Chen, Ting; Huang, Ya-Qing; Zhang, Lian; Huang, Zhi-Chun; Liu, Bin; Yang, Ming (Frontiers in Neurology, 2018)
Objective To explore the change of interhemispheric functional coordination in patients with obstructive sleep apnea-hypopnea syndrome（OSAHS）applying a novel voxel-mirrored homotopic connectivity (VMHC) method. Methods 29 patients with OSAHS and 26 sex-, age- and eduction-comparable normal controls were recruited and resting-state functional magnetic resonance imaging (rs-fMRI) data were obtained.We employed VMHC method to analyze the interhemispheric functional connectivity difference between OSAHS and healthy controls. Z-value of altered VMHC in brain regions were correlated with clinical characteristics. Results The patients with OSAHS had significantly higher scores for BMI (t = 5.749, P < .001), AHI (t = 7.706, P < .001), ODI (t=6.041, P < .001), and ESS (t=3.711, P < .001), but significantly lower scores for CFT-immediate recall (t = -3.727, P < .05) when compared to the controls.The VMHC revealed significant increase in bilateral calcarine and precuneus in OSAHS patients in comparation with normal controls. Futhermore,there were significantly positive correlations between apnea hyponea index (AHI) and VMHC coefficients of calcarine and precuneus (r = .399, p = .032; r = .378, p = .043). Conclusion The study found that the OSAHS patients were along with memory weakness,the correlation between abnormal VMHC and AHI in OSAHS patients suggested AHI might be a key factor of cognitive dysfunction,which might give new insights into the underling neural pathophysiology of OSAHS-related cognitive deficits.